2008
DOI: 10.1002/eji.200838918
|View full text |Cite
|
Sign up to set email alerts
|

From phagocyte diversity and activation to probiotics: Back to Metchnikoff

Abstract: In this issue of the European Journal of Immunology, Siamon Gordon gives a detailed account of Metchnikoff's life and his achievements (Eur. J. Immunol. 2008. 38: 3257-3264). Looking back at the roots of innate immunity stimulates reflections on open issues in the field. Here, I give a personal view of some of these issues, including myeloid-derived suppressor cells, macrophage polarization and adaptive responses of mononuclear phagocytes. Key words: Macrophage activation Á Macrophages Á M1/M2 polarization Á P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 56 publications
1
52
0
1
Order By: Relevance
“…If the latter explanation is true, then EPS could be considered a bona fide beneficial immunomodulator. In summary, the comparative analysis of ␤-glucan-producing and nonproducing strains performed in this work has provided insights into the debated issues of probiotic properties of EPSproducing LAB (3) and the role of EPS in the immunomodulation of macrophages (20).…”
Section: Figmentioning
confidence: 94%
“…If the latter explanation is true, then EPS could be considered a bona fide beneficial immunomodulator. In summary, the comparative analysis of ␤-glucan-producing and nonproducing strains performed in this work has provided insights into the debated issues of probiotic properties of EPSproducing LAB (3) and the role of EPS in the immunomodulation of macrophages (20).…”
Section: Figmentioning
confidence: 94%
“…24 In vivo counterparts of M2 macrophage polarization have been observed in tissue remodeling during ontogeny, 29 in placenta, 30 and in various pathological conditions. 20,31 The M1/M2 macrophage polarization paradigm should be viewed in the light of the plasticity and flexibility of mononuclear phagocytes mirroring the Th1/ Th2 paradigm and their activating products (IFN␥ and IL-4). 20 Indeed, different signals give rise to a complex multidimensional variety of macrophage activation profiles.…”
Section: Macrophage Activation and Polarizationmentioning
confidence: 99%
“…20,31 The M1/M2 macrophage polarization paradigm should be viewed in the light of the plasticity and flexibility of mononuclear phagocytes mirroring the Th1/ Th2 paradigm and their activating products (IFN␥ and IL-4). 20 Indeed, different signals give rise to a complex multidimensional variety of macrophage activation profiles. 3,22 The relation between monocyte subsets and macrophage polarization remains unclear.…”
Section: Macrophage Activation and Polarizationmentioning
confidence: 99%
“…4,8,47 Classically activated macrophages (M1 cells) mediate resistance to intracellular pathogens through the expression of cytokines and chemokines such as IL-12, CXCL9 and CXCL10, which promote the Th1 dominant response. [48][49][50] In contrast, alternatively activated macrophages (M2 cells) are critically involved in granuloma formation and fibrosis via the Th2 cytokine response. 19,43,[51][52][53][54] Recent studies revealed that the polymorphic dense granule protein GRA15 II and rhoptry protein ROP16 I/III secreted by type II or type I/III Toxoplasma induced differential macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%